A blended e-health intervention for improving functional capacity in elderly patients on haemodialysis: A feasibility study - Damiano D. Zemp; Damiano D. Zemp; Pierrette Baschung Pfister; Pierrette Baschung Pfister; Ruud H. Knols; Ruud H. Knols; Ruud H. Knols; Pierluigi Quadri; Pierluigi Quadri; Giorgia Bianchi; Davide Giunzioni; Soraya Lavorato; et al. (Frontiers Media S.A., 2022)
IntroductionPhysical exercise showed to be beneficial for frail older adults on haemodialysis (HD). However, there are several obstacles hindering the regular practice of exercise, such as transportation difficulties, lack of time, fatigue and comorbidities. E-health in this regard has many potential advantages and could be useful for motivating HD patients to increase their level of physical activity. The aim of this study was to evaluate the feasibility of a blended e-health intervention for elderly HD patients who individually exercise at home while under remote supervision of a physiotherapist.Material and methodsPatients over 60 years of age with sufficient cognitive and motoric resources to perform a simple physical test battery and to use a tablet-computer were recruited from four HD outpatient facilities. Following baseline assessment at home, the participants were visited by a physiotherapist (PT). The PT set an individual exercise programme and explained how to use the web-based interface. During the 12 weeks of training, the PTs remotely supervised the patients' progress. At 12 weeks follow-up a second assessment took place.ResultsTwenty-two patients were recruited to participate in the study. Seven patients dropped out of the blended programme and 15 patients concluded the programme. The average training frequency of the 15 participants concluding the study was 1.5 times a week [range 0.2-5.8]. The duration of a training session was between 20 and 40 min. The usability of the system was deemed positive. Regarding the efficacy of the intervention, no significant improvement of any measured parameter was found, and effect sizes were small to medium.ConclusionA blended e-health intervention supported by a web-based application for exercising at home under remote supervision of a PT is feasible in a HD population including older patients. However, before planning a randomized controlled trial, strategies to increase the recruitment rate and the adherence to such a blended intervention should be further developed, e.g., to improve the recruitment procedures and lower the expectable drop-out rate. Furthermore, the dosage of the blended programme should be adapted to the patients' physical performance levels in future trials.The study was registered on the website clinicaltrials.gov with ID NCT04076488.